1999
DOI: 10.1121/1.427952
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of spoken words by native and non-native listeners: Talker-, listener-, and item-related factors

Abstract: In order to gain insight into the interplay between the talker-, listener-, and item-related factors that influence speech perception, a large multi-talker database of digitally recorded spoken words was developed, and was then submitted to intelligibility tests with multiple listeners. Ten talkers produced two lists of words at three speaking rates. One list contained lexically "easy" words (words with few phonetically similar sounding "neighbors" with which they could be confused), and the other list contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
210
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(230 citation statements)
references
References 29 publications
17
210
2
1
Order By: Relevance
“…Therefore, during bilingual processing, cross-linguistic competitors with high-density neighborhoods may be less likely to become co-activated than cross-linguistic competitors with low-density neighborhoods. Furthermore, studies of auditory word recognition have suggested that non-native speakers experience particular difficulty recognizing words with high-density neighborhoods (Bradlow and Pisoni 1999;Takayanagi et al 2002). This difficulty may explain absence of high-density competitor activation in the non-native group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, during bilingual processing, cross-linguistic competitors with high-density neighborhoods may be less likely to become co-activated than cross-linguistic competitors with low-density neighborhoods. Furthermore, studies of auditory word recognition have suggested that non-native speakers experience particular difficulty recognizing words with high-density neighborhoods (Bradlow and Pisoni 1999;Takayanagi et al 2002). This difficulty may explain absence of high-density competitor activation in the non-native group.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from other within-language recognition studies suggests that large neighborhood size yields increased competition and delayed selection of the target word. In contrast, small neighborhood size yields reduced competition and speeds up recognition of the target word (e.g., Bradlow and Pisoni 1999;Garlock et al 2001;Luce and Pisoni 1998;Vitevitch and Luce 1998;Ziegler et al 2003). Therefore, during auditory word recognition, low-density words are activated more readily than high-density words.…”
Section: Experiments 2: Effect Of Within-and Across-language Phonologimentioning
confidence: 99%
See 1 more Smart Citation
“…However, such studies need to be carefully designed in terms of the selection of tokens and listeners. Although native speakers are attuned to the acoustic properties of English /ɹ/ (e.g., F3, F2, F1, transition duration), their sound and word recognition patterns are also subject to the influence of lexical factors, such as text frequency and neighbourhood density (Bradlow & Pisoni, 1999) and familiarity with accented speech (Kennedy & Trofimovich, 2008). Furthermore, it might be relatively difficult for human listeners to accurately evaluate the quality of particular L2 sounds and words embedded in spontaneous speech samples because their judgments would likely be affected by not only phonological but also lexical, morphosyntactic, and pragmatic use of language (Piske et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies [16,17] have shown that there is also a role for listener-specific factors in perception of foreign-accentedness. Specifically, the role of native versus non-native status of the listener in the perception of talker accentedness has been the focus of a number of studies e.g, [18,19,20].…”
Section: Introductionmentioning
confidence: 99%